2001
DOI: 10.1023/a:1011115107615
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-receptor-directed neoadjuvant therapy for breast cancer: Results of a randomised trial using formestane and methotrexate, mitozantrone and mitomycin C (MMM) chemotherapy

Abstract: In this study neoadjuvant treatment with endocrine or chemotherapy provided no obvious survival benefit to women with breast cancer. However, it does allow avoidance of surgery in some cases. Also, the patients whose tumours respond to neoadjuvant systemic therapy have a lower incidence of distant metastases after five year follow-up compared to those whose tumours fail to respond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 17 publications
0
26
1
Order By: Relevance
“…c restricted to postmenopausal women. Data arising from very small studies have been reported in premenopausal women treated with preoperative GnRH analogue (Gazet et al, 2001;Miller et al, 2001). Aromatase inhibitors in combination with GnRH analogue have not been systematically studied as primary therapy in premenopausal women with hormone receptor positive locally advanced operable breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…c restricted to postmenopausal women. Data arising from very small studies have been reported in premenopausal women treated with preoperative GnRH analogue (Gazet et al, 2001;Miller et al, 2001). Aromatase inhibitors in combination with GnRH analogue have not been systematically studied as primary therapy in premenopausal women with hormone receptor positive locally advanced operable breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature (Eiermann et al, 2001;Gazet et al, 2001;Smith et al, 2005), we expected to observe at least 45% of clinical responses. We adopted an optimal two-stage design, with a target rate of clinical responses of 45% deemed acceptable, and a response rate of 22% considered unacceptable.…”
Section: Methodsmentioning
confidence: 98%
“…48 Neoadjuvant endocrine therapy has not been recommended for younger women outside of clinical trials 52,53 ; however, preliminary data suggest that neoadjuvant endocrine therapy can be effective in premenopausal women. 54 Specifically, for ER-positive/Her2-negative premenopausal women, gonadotropin-releasing hormone agonist (GnRH, goserelin) plus aromatase inhibitor therapy (letrozole or anastrozole) achieved overall response rates ranging from 50% to 70% and were more effective than GnRH agonist in combination with tomoxifen. [54][55][56][57] Data from several trials have shown that young age at diagnosis was an independent predictive factor for pathologic complete response (pCR) after neoadjuvant chemotherapy.…”
Section: Treatmentmentioning
confidence: 99%
“…54 Specifically, for ER-positive/Her2-negative premenopausal women, gonadotropin-releasing hormone agonist (GnRH, goserelin) plus aromatase inhibitor therapy (letrozole or anastrozole) achieved overall response rates ranging from 50% to 70% and were more effective than GnRH agonist in combination with tomoxifen. [54][55][56][57] Data from several trials have shown that young age at diagnosis was an independent predictive factor for pathologic complete response (pCR) after neoadjuvant chemotherapy. Meta-analysis of 8 German neoadjuvant breast cancer studies involving more than 3300 women demonstrated that pCR correlates with outcome in breast cancer.…”
Section: Treatmentmentioning
confidence: 99%
“…In an early study by Gazet et al (2001), 13 premenopausal women with ER+ breast cancer received neoadjuvant goserelin, a gonadotropin-releasing hormone (GnRH) analogue. At 3 months, seven of the 13 women had an overall response by clinical assessment, suggesting that premenopausal women may also benefit from neoadjuvant endocrine manipulation (Gazet et al , 2001).…”
Section: Preoperative Endocrine Therapy In Premenopausal Womenmentioning
confidence: 99%